Employees’ Attitude toward the Implementation of Open Selection System for Senior Executive Service Positions - Sakinah, Nada (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
The Civil Service Law has become the foundation for government’s human resource management reform. One of the major changes that the law brought about was the open selection for the filling of senior executive positions. The attitude of the parties affected by the changes is a factor that determines the success of a reform. Taking a case of the Indonesian Ministry of Energy and Mineral Resources as one of pioneering government ministries that has implemented such reform, this research aims at describing the attitude of civil servants of the ministry toward the open selection policy for senior executive positions, particularly first level senior executives service (jabatan pimpinan tinggi/JPT Pratama), as well as to describe the attitude differences that are showed by the officers based on their age, gender, education level, position type, and service length in the ministry. As a result, there is generally a positive attitude without significant differences between the officers in terms of age, gender, and different position type, but there are also partial differences between one group and another based on education level and service length.